From Structural Analysis of Semiotics QS. Al-'Alaq 1-5 to Basic Structure of Science in Islamic Education - Rahayu Subakat; Sangkot Sirait; Fakhruddin Faiz; Mustafa Kamal Nasution (IAIN Ponorogo, 2022)
Philosophically, QS. al-'Alaq: 1-5 forms the basic structure of science as the foundation for the development of Islamic education. This study aims to explain the relationship between QS. al-'Alaq: 1-5 with the basic structure of Science and its implications in Islamic education. This study uses secondary data sources, namely the Koran, classic, modern and contemporary. Methods of collecting data with documentation, data analysis using content analysis with stages; descriptive, explanative, discursive, interpretative, and implicative. This study indicates that the basic structure of Science in QS. al-'Alaq: 1-5 includes; epistemology, world view, and ideology. The basic structure of Science in QS. al-'Alaq: 1-5 is the relationship between spirituality awareness, rationality awareness, ethical awareness, scientific awareness, and awareness of social transformation. Thus, practically QS. al-'Alaq: 1-5 can be used as an epistemological basis for the development of Islamic education.